Physiotherapy for Children with Cerebral Palsy - Verizka, Talitha; Berawi, Khairun Nisa; Happy, Terza Aflika; Oktarlina, Rasmi Zakiah; Fiana, Dewi Nur (Medula, 2024)
Cerebral cortex has a motoric area which function in controlling muscle movement. When this area does not develop properly or damaged, cerebral palsy can occur. Cerebral palsy is a disorder of the motoric area of the brain which causes a dysfunction on muscle activities. Eventually, this will lead to limitation of daily activities. Disorder can occur in prenatal, perinatal, or postnatal period. There are four types of cerebral palsy which are spastic, dyskinetic, ataxic, and mixed cerebral palsy. Patient with cerebral palsy experience changes in production of force, balance, and gait as well as a decreased in production of volunteer force. The most dominant sign is balance disorder, but sensoric deficiency could also be seen. In diagnosing cerebral palsy, Levine criteria called POSTER can be used. A child is said to have cerebral palsy when four out of six categories are fulfilled. The aim of treatment of cerebral palsy is to increase functionality, improve capability, and sustain health. Treatment should be done as early as possible and intensive to achieve maximum output. Aside from pharmacological and surgical treatment, mechanic aids, and management of associated medical condition, treatment of cerebral palsy includes physiotherapy. Physiotherapy helps to improve gross motor quality in children with cerebral palsy. Although there are no medicines that can cure cerebral palsy, physiotherapy approach can be done includes re-patterning movement, neurodevelopmental technique (NDT), body weight support treadmill training, atlanto-occipitalisi mobilisation, and standing frame exercise.